68Ga-DOTATOC PET/CT in the Localization of Pituitary Tumors in Cushing’s Disease - Kim, Kyungwon; Kim, Dongwoo; Lee, Min-Ho; Park, Yae Won; Ahn, Sung Soo; Moon, Ju Hyung; Kim, Eui Hyun; Kim, Sun Ho; Ku, Cheol Ryong; Lee, Eun Jig (Endocrinology and metabolism (Seoul), 2025)
Background: This study aimed to determine the value of 68Ga-DOTATOC positron emission tomography/computed tomography (PET/CT) in localizing adrenocorticotropic hormone (ACTH)-secreting pituitary adenomas.Methods: In this retrospective cohort study, we enrolled 30 patients with Cushing’s disease and positive ACTH immunoreactivity. All patients underwent 68Ga-DOTATOC PET/CT and pituitary magnetic resonance imaging (MRI) before transsphenoidal adenomectomy.Results: Twenty-five patients showed 68Ga-DOTATOC uptake in their pituitary glands on PET/CT. Median age, pre-operative ACTH levels, pre-operative cortisol, and tumor size on MRI were comparable irrespective of DOTATOC uptake. 68Ga-DOTATOC PET/CT showed a 77% success rate for localizing adenomas, which was not statistically different from that of MRI. The ACTH level in the successful localization group was significantly higher than that in the failed group (84.41 pg/mL vs. 37.26 pg/mL, P=0.001). The ACTH level was statistically significant predictor of successful localization using 68Ga-DOTATOC PET/CT (P=0.013). The area under the curve was 0.932 with a cutoff of 53.86 pg/mL for ACTH levels to determine successful localization. Pre-operative ACTH levels above 53.86 pg/mL showed the best diagnostic accuracy in predicting the success of localizing adenomas (sensitivity, 91.3%; specificity, 85.7%). Mean and maximum standardized uptake value of adenoma negatively correlated to pre-operative ACTH level.Conclusion: Plasma ACTH level is a favorable predictor for the successful localization and negative correlation with 68Ga-DOTATOC uptake of corticotroph adenomas in 68Ga-DOTATOC PET/CT. 68Ga-DOTATOC PET/CT did not improve tumor localization for Cushing’s disease compared with MRI alone.